2017
DOI: 10.1053/j.gastro.2017.03.035
|View full text |Cite
|
Sign up to set email alerts
|

SP and KLF Transcription Factors in Digestive Physiology and Diseases

Abstract: Specificity proteins (SPs) and Krüppel-like factors (KLFs) belong to the family of transcription factors that contain conserved zinc finger domains involved in binding to target DNA sequences. Many of these proteins are expressed in different tissues and have distinct tissue-specific activities and functions. Studies demonstrate that SPs and KLFs regulate not only physiological processes such as growth, development, differentiation, proliferation, and embryogenesis, but pathogenesis of many diseases, including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
78
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 85 publications
(78 citation statements)
references
References 302 publications
0
78
0
Order By: Relevance
“…Our previous studies identified KLF6 as most abundantly expressed in myeloid cells and essential for classic macrophage activation (23). Studies by our group and others have shown that KLF6 contributes to a variety of human inflammatory disease conditions (25,42). Studies by Qi et al (43) implicated role for KLF6 in the early onset of diabetes utilizing rat model system.…”
Section: Discussionmentioning
confidence: 93%
“…Our previous studies identified KLF6 as most abundantly expressed in myeloid cells and essential for classic macrophage activation (23). Studies by our group and others have shown that KLF6 contributes to a variety of human inflammatory disease conditions (25,42). Studies by Qi et al (43) implicated role for KLF6 in the early onset of diabetes utilizing rat model system.…”
Section: Discussionmentioning
confidence: 93%
“…Krüppel-like zinc-finger transcription factor (TF) KLF5 is expressed in both ISCs and transit-amplifying (TA) [13][14][15] cells and regulates epithelial proliferation, differentiation, and development. 13,16 Conditional Klf5 deletion from the entire mouse intestinal epithelium, using Villin-Cre as a driver, impairs epithelial cell proliferation.…”
mentioning
confidence: 99%
“…Previous studies showed that Sp4 is overexpressed in pancreatic, bladder, esophageal, breast, prostate, lung, colon, epidermal, thyroid, and rhabdomyosarcoma cancer cell lines and multiple myeloma cell lines, and KD of Sp4 significantly decreases cell growth and migration and induces apoptosis in nine cancer cell lines derived from six different tumors, [ 18,19 ] suggesting that Sp4 is a pro‐oncogene. However, the different Sp4 splicing variants were not considered in these studies; only L‐Sp4 splicing variants were considered.…”
Section: Discussionmentioning
confidence: 99%